PENGORGANISASIAN SECARA PERSONAL DAN GEJALA INDIVIDUALISASI ORGANISASI SEBAGAI KARAKTER UTAMA PENGORGANISASIAN DIRI PETANI DI INDONESIA (Forum Penelitian Agro Ekonomi, 2016)
Explaining how farmers conduct their farm business is trapped in organization theory and analysis, so far. This paper applies concept and theory of new institutionalism understanding which focuses social relation as the most basic object of analysis. It is found that farmers’ organizations in Indonesia are unique indicated by organization individualization as the real fact of formal farmers’ organization. This symptom is not observed if it employs organization analysis. It comes from the previous farmers’ organizations before the formal organization is acknowledged, namely personalized organizing. These two findings are based on recognizing that farmers are rational, creative social actors using all institution and organization resources for running their farm business. In the future, empowering farmers is carried out through offering other types than formal organization for more effective social relation.